2009
DOI: 10.1007/s11033-009-9644-x
|View full text |Cite
|
Sign up to set email alerts
|

SINE indel polymorphism of AGL gene and association with growth and carcass traits in Landrace × Jeju black pig F2 population

Abstract: Genetic polymorphisms in the glycogen debrancher enzyme (AGL) gene were assessed with regard to their association with growth and carcass traits in the F2 population crossbred Landrace and Jeju (Korea) Black pig. Three genotypes representing the insertion and/or deletion (indel) polymorphisms of short interspersed nuclear element were detected at frequencies of 0.278 (L/L), 0.479 (L/S), and 0.243 (S/S), respectively. The AGL S allele-containing pigs evidenced significantly heavier body weights at birth, the 3r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Functional deficiency of AGL activity leads to an autosomal recessive human disease called glycogen storage disease type II, characterized by a variety of symptoms, one of which is growth retardation. In pigs, the AGL gene is associated with traits such as growth, carcass weight and backfat thickness (Han et al. 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Functional deficiency of AGL activity leads to an autosomal recessive human disease called glycogen storage disease type II, characterized by a variety of symptoms, one of which is growth retardation. In pigs, the AGL gene is associated with traits such as growth, carcass weight and backfat thickness (Han et al. 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The F 2 population was generated via reciprocal intercrosses between Landrace and JBPs. In a previous study, the authors reported in detail on F 2 animal production (Han et al, 2010); blood, muscle, and tail samples were collected from F 2 animals. All experimental procedures were conducted at the Subtropical Animal Experiment Station of the National Institute of Animal Science, Rural Development Administration of South Korea.…”
Section: Methodsmentioning
confidence: 99%
“…The copy number variation regions CADM2-CNV1 and CADM2-CNV2 are located at 33,143,512-33,379,427 bp and 33,569,316-33,629,746 bp from the reference genome sequence NC_037328.1, respectively ( Figure 1). Animals 2019, 9,1008 3 of 11 LIHPS-CAAS-2017-115). Blood sample collection and body measurements were performed in strict accordance with the guide for the Care and Use of Laboratory Animals.…”
Section: Genomic Dna Extraction and Copy Number Identificationmentioning
confidence: 99%
“…More than 99% of indels are less than 50 bp in length [6,7], and some long insertions and deletions are returned into the concept of structural variation [8]. As a genetic marker, indels have great potential whether in growth and reproduction traits or the treatment of disease [9][10][11]. However, CNVs include duplication and/or deletions of DNA fragments ≥50 kb, and can cause a greater number of differences than SNPs and indels [12], which can be discovered by clone-based array comparative genome hybridization (array-CGH) [13].…”
mentioning
confidence: 99%